APLIKASI MEDICAL APPOINTMENT PADA DJINGGA MEDIA TEKNOKREATIF - Saputra, I Made Widi Arsa Ari Saputra; I Wayan Supriana; Cokorda Rai Adi Pramartha (Jurnal Pengabdian Informatika, 2025)
The Covid-19 outbreak has left many new conditions in society. One of them is people's fear of visiting hospitals which are considered prone to viruses and germs. The lack of public knowledge regarding the symptoms of a disease, and Bali's position as a potential source of foreign virus transmission due to the tourism sector is one of the problems in society today. Medical Appointment is an application in the form of a website which is intended to facilitate the public with doctors to make appointments. This application is useful for people who do not know the contact person of a specialist doctor. With this application, it will help people to contact the desired doctor to make appointments and check-ups regarding the problems they are facing.